The improvement of thermal stability and adhesion of silicone rubber composites modified by phenolic epoxy resin. Issue 5 (4th May 2019) - Yan, Liwei; Zhang, Bin; Wang, Yuan; Zhou, Cheng; Li, Rui; Luo, Wei; Chen, Yang; Zou, Huawei; Liang, Mei
Abstract: The phenolic epoxy resin (F51) was siliconized by KH550 and the product was named as FKS. A hydroxyl-terminated polydimethylsiloxane (HTPDMS) which was modified with FKS was prepared. The siliconization reaction ensured a segment of siloxane on the side chain of F51. FT-IR and 1 H-NMR were employed to confirm the chemical structure of FKS. Morphology observations revealed that the enhancement of mechanical properties of the silicone rubber systems can be attributed to good compatibility between FKS and silicone rubber matrix. Thermogravimetric analysis showed that the residual yield at 800 °C of silicone rubber composites increased significantly when compared with that of neat HTPDMS. The mechanical properties demonstrated that tensile strength and elongation at break of silicone rubber system increased distinctly after modification, especially when 30 phr siliconized F51 were added to the silicone rubber. Shear strength was improved gradually with the addition of FKS. These above observations emphasize the vital effect of FKS on the behavior of modified HTPDMS.